Improved characterization of the pharmacokinetics of acalabrutinib and its pharmacologically active metabolite, ACP‐5862, in patients with B‐cell malignancies and in healthy subjects using a population pharmacokinetic approach. Issue 2 (21st August 2021) - Edlund, Helena; Bellanti, Francesco; Liu, Huan; Vishwanathan, Karthick; Tomkinson, Helen; Ware, Joseph; Sharma, Shringi; Buil‐Bruna, Núria
Abstract : This analysis aimed to describe the pharmacokinetics (PK) of acalabrutinib and its active metabolite, ACP‐5862. A total of 8935 acalabrutinib samples from 712 subjects and 2394 ACP‐5862 samples from 304 subjects from 12 clinical studies in patients with B‐cell malignancies and healthy subjects were analysed by nonlinear mixed‐effects modelling. Acalabrutinib PK was characterized by a 2‐compartment model with first‐order elimination. The large variability in absorption was adequately described by transit compartment chain and first‐order absorption, with between‐occasion variability on the mean transit time and relative bioavailability. The PK of ACP‐5862 was characterized by a 2‐compartment model with first‐order elimination, and the formation rate was defined as the acalabrutinib clearance multiplied by the fraction metabolized. Health status, Eastern Cooperative Oncology Group performance status, and coadministration of proton‐pump inhibitors were significant covariates. However, none of the investigated covariates led to clinically meaningful changes in exposure, supporting a flat dosing of acalabrutinib.